PRODUCT DIVERSIFICATION AS A MEANS TO ENHANCE THE ECONOMIC STABILITY OF ENTERPRISES (Western European Journal of Medicine and Medical Science, 2024)
This article discusses the issues of market modification through increasing sales volumes, gaining consumer trust, introducing products to new market segments, focusing customers’ attention and interest on the products produced by the company, and encouraging customers to intensively consume these products.